Early syphilis in pregnant woman and prozone phenomenon in serology: case report - Reis, Helena Lucia B; Chambô Filho, Antônio; Sabino, Josilaine B; Caldellas, Sabrina (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: the incidence of adult syphilis and the congenital syphilis are raised in Brazil, being some of the causes to increase infantile death rate. Objective: this study aims at relating a recent syphilis case, in a second trimester pregnant woman, with serum prozone phenomenon, identified during attendance in the Maternidade da Santa Casa de Misericórdia de Vitória, Espírito Santo. Methods: case report related during attendance in October of 2007, at Maternitdade da Santa Casa de Misericórdia de Vitória, Espírito Santo State. Results: the patient presented papulosa sifilides in her external genital area and macular exanthema in the abdominal and back regions, with no gauged fever. The VDRL was negative with pure serum. After dilution it was reagent till up to 1/128 characterizing, thus, prozone phenomenon. The FTA-Abs treponemic test was positive and the anti-HCV, HBsAg and the anti-HIV were no reagent. Conclusion: the health professional must be capable for clinical diagnosis of syphilis and be attentive to the possibility of prozone phenomenon occurrence in patients with papulosa sifílides. Serum dilution is always recommended for the correct syphilis laboratorial diagnosis and to institute adjusted treatment in pregnant woman with syphilis, as well as for the sexual partner, as early as possible.